Exploring EFL Business-Major College Students’ Imagined Communities, Perceptions of English, and Their Agency - Pei-Chia Liao (Widya Mandala Surabaya Catholic University, 2022)
Highlighting technology as a site for learners’ agency, this study attempts to contribute new knowledge in EFL learning in out-of-classroom contexts, which is the little-explored area in the TESOL field. This study employs qualitative case studies to explore EFL business college students’ perspectives on English and their imagined communities. It examines how their imagined communities shaped their current language practices and investment in language learning. It also offers an analysis of the interconnectedness of the students’ perspective on English as capital and their agency. The findings demonstrate that for EFL business-major college students, English embodies more than its linguistic power; it is often associated with symbolic and economic value. Taking the students’ personal histories and aspiration into account, the study points that imagined communities played a vital role in shaping the participants’ learning trajectories, as well as inspiring and directing them into who they wanted to be or become. It also shows that the students were highly aware of the resources associated with their target language(s), and they strived to gain those resources. Furthermore, the study reveals that the students exercised their agency using myriad forms of technology to engage in their imagined communities. Implications for language classrooms will also be discussed.